Pengaruh Aplikasi Fiber Braided Polyethylene Terhadap Kekuatan Tekan Resin Komposit Nanofil - Firda, Afifa Zahratu, drg. Noor Hafida Widyastuti, Sp.KG, drg. Juwita Raditya Ningsih (2016)
Nanofilled composite resin is known has lower compressive strength than microhybrid and microfilled composite resin. The compressive strength has an important role for mastication process. Fatigue fracture is a factor which has been considered the cause of restoration failure. An altenative material to strengthen dental resins is fiber. Braided polyethylene fiber has been commonly used in dentistry because it has good aesthethic, strengthen composite restorative materials, increases strength and modulus of elasticity. The purpose of this research is to understand the effect of placing braided polyethylene fiber on compressive strength of nanofilled composite resin. The research finding was initiated by making samples for control and experimental group. It was then be measured for compressive strength. Samples were prepared in a costumized cylinder acrylic mould of 4 mm diameter and 8 mm height. Control group were made of nanofilled composite resin without braided polyethylene fiber, and experimental group were made of nanofilled composite resin with braided polyethylene fiber as reinforcing material. Samples were exposed by light curing unit for 20 seconds. All specimens were immersed in aquades and incubated at 37°C for 24 hours. The compressive strength test was determined by using Universal Testing Machine at 1 mm/min crosshead speed. The results were statistically analyzed by using independent sample t-test. The statistic results showed p=0.504 (p>0.05). The conclusion of the research showed that braided polyethylene fiber has no effect on compressive strength of nanofilled composite resin.